Psyllids, Africa beware! - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
A two-pronged attack on the ravages of the Leucaena psyllid (Heteropsylla cubana) in Asia was formulated at a workshop on the pest held in Bogor, Indonesia, in January 1989, and attended by more than 60 scientists from ten countries. Scientists...